A Case Report of Dublin-Johnson Syndrome - Amir Hooshang Mohammad Alizadeh (پزشکی بالینی ابن سینا, 2000)
Hyperbilirubinemia is a common manifestation in internal medicine. It is divided to conjugated and unconjugated hyperbilirubinemia . Conjugated hyperbilirubinemia usually results from hepatocellular or cholestatic liver disease or from extrahepatic biliary obstruction. Isolated conjugated hyperbilirubinemia is the primary manifestation of two heritable disorders, Rotor and Dublin – Johnson syndromes, and can also be seen in some patients with the syndrome of recurrent benign intrahepatic cholestasis.